Photodetector Based on Titanium Oxide Nanoparticles Produced via Pulsed Laser Ablation - Ban A. Bader; Iman H. Hadi; Muna Y. Slewa; Khawla S Khashan; Farah A. Abdulameer (Advances in Condensed Matter Physics)
TiO2 nanoparticles (NPs) were produced via utilized nanosecond laser ablation of titanium in water. The description of these NPs was employed utilizing XRD, SEM, and UV-VIS. Then, optoelectronic properties were investigated via a drop-casting of TiO2 NPs on the Si wafer substrate. XRD results show the formation of anatase TiO2. The SEM exhibits a spherical shape with sizing changing from 5 nm to 50 nm. The bandgap was 3.6 eV which was determined from the Tauc chart. The IV characteristic of the TiO2NPs/Si heterojunction showed good rectifying behaviour, with a maximum responsivity of about 0.7 A/W at 310 nm.